Pendampingan UMKM Gula Merah dan Buah Naga Melalui Olah Sinara - Biati, Lilit; Suprapto, Ribut; Fikri, Muhammad Kanzul (Proceedings of Annual Conference on Community Engagement, 2022)
The number of brown sugar producers and dragon fruit farmers in Kandangan Village contributes to a prosperous economy for the community. the idea arose to process the two ingredients into a beverage product with high economic value. With proper processing, will have good prospects. The strategy using the PAR (Participation Action Research) method is an Economic-Based Community Service, providing community assistance in Kandangan Village, especially Krajan hamlet. After observing and implementing community service programs, it can be identified that there is potential that can be developed in Kandangan Village, namely brown sugar and dragon fruit. After the empowerment of the community through the use of brown sugar and dragon fruit into SINARA to increase the selling value of red guala and dragon fruit in Kandangan Village, it began with training and outreach to the community as a way to increase people's income, and the willingness to be entrepreneurial so as to improve human resources. independent and prosperous.